Effect of a fruit and vegetable drink on muscle recovery after resistance exercise - Maria Hipólito Almeida Pinheiro; Luan Pereira Fonseca; Jeann Carlo Gazolla de Oliveira; Gotardo do Carmo de Castro; Vitor Hugo Santos-Rezende; Mariana da Silva Gouveia; Bruna Dias Viveiros; Eliane Maurício Furtado Martins; Frederico Souzalima Caldoncelli Franco; João Batista Ferreira-Júnior (Hospital de Clínicas de Itajubá, 2022)
Objective: To evaluate the effect of fruit and vegetable drink supplementation on muscle recovery after resistance exercise. Methods: 11 men performed two experimental conditions 12 days apart, in a randomized and double-blind manner: 1) Supplementation with Smoothie - drink based on pineapple, mint, sage, ginger, and pomegranate; and 2) Placebo - drink based on artificial pineapple juice. Participants ingested 400 mL of Smoothie or Placebo drinks daily for 9 days, starting one week before performing the exercise (10 sets of 10 unilateral maximum repetitions in leg press 45º). The perceived subjective recovery (PSR), thickness (MT) and soreness (MS) in the anterior thigh muscles, and maximum isometric strength (MIS) were measured before, 24, 48, 72, and 96 h after exercise. Results: There was a reduction in MIS and PSR and an increase in MS 24 h after exercise (p < 0.05). In both situations, MIS returned to baseline values at 72 h (p > 0.05), while PSR and MS returned to baseline values 96 h after exercise. There was no change in MT (p > 0.05). Conclusion: Supplementation with pineapple, mint, sage, ginger, and pomegranate drinks did not accelerate muscle recovery over 96 h after the 45º leg press exercise.